Principles of semiconductor devices - Dimitrijev, Sima, 1958- (Oxford University Press, 2012)
"This dynamic text applies physics concepts and equations to practical, real-world applications of semiconductor device theory"-- Provided by publisher
Keywords: Semiconductors.; elektronické knihy; electronic books